Interleukins 4 and 21 Protect Anti-IgM Induced Cell Death in Ramos B Cells: Implication for Autoimmune Diseases - Hui, Chin Wai; Wu, Wai Chung; Leung, Shui On (Frontiers in Immunology, 2022)
Interleukins 4 (IL-4) and 21 (IL-21) belong to the common gamma chain cytokine family which are highly involved in the progression of autoimmune diseases. While IL-4 is well known to be involved in the suppression of apoptosis of autoreactive B cells, the role played by IL-21 remains unclear. In the current study, we activated the human Burkitt’s lymphoma Ramos B cells with anti-IgM to mimic B cell hyperactivation observed in patients of autoimmune diseases. Consistent with other reported findings, anti-IgM led to the downregulation of proteins involved in B cell survival and proliferation, as well as the activation of caspase 3 activity and DNA damage, resulting in apoptotic cell death after 48-hour treatment. Although both IL-4 and IL-21 reversed anti-IgM-induced apoptosis and cell cycle arrest, they did so via different mechanisms: while IL-4 could directly suppress anti-IgM-induced caspase 3 activation and marker indicative of DNA damage, IL-21 could induce B cell proliferation in the presence of anti-IgM. Importantly, IL-21 also suppressed activation induced cell death in human primary B cells. Pre-treatment with clinically validated JAK inhibitors completely reversed the effects of IL-4 and IL-21 to rescue anti-IgM induced cell death and DNA damage. The results indicate the underlying mechanisms of how IL-4 and IL-21 differentially promote survival of hyperactivated B cells and provide hints to treat autoimmune diseases.